Komitmen Indonesia dalam Mematuhi Perjanjian Kerjasama REDD+ Indonesia-Norwegia terhadap Upaya Penanganan Deforestasi dan Degradasi Hutan di Indonesia - Satwika, Wira Fadhil; Putranti, Ika Riswanti (Journal of International Relations, 2020)
This research aims to explain commitments of the Indonesian government in complying with the REDD + Partnership between Indonesia and Norway towards the ef orts and policies of the Indonesian government to deal with deforestation and forest degradation problems. Indonesia has been long facing the issues of deforestation and forest degradation occurring along with the development of industrial activities at home and worldwide. Indonesia seeks to overcome these problems by among others establishing cooperation with Norway in the REDD + Partnership scheme, in which Indonesia is willing to contribute in reducing carbon gas emissions from the causes of deforestation and forest degradation, while Norway is willing to pay Indonesia for its performance in the environmental conservation worth of US $ 1 billion, starting from 2010. This research uses compliance theory as a perspective to analyze the commitments of the Indonesian government. This research also tries to explain which factors make the two countries agreed to comply with the partnership, and so that it can be known the type of compliance that Indonesia shows with the partnership. In addition, this research also provides an analysis of the sustainability of this partnership, which the process is still ongoing. It is recommended that Indonesia and Norway partnership in environmental protection would go further after REDD+ implementation in Indonesia for the sake of reducing deforestation and forest degradation in Indonesia.